Resistance of Trypanosome species isolated from cattle populations in Lambwe Valley, Kenya, to diminazene aceturate - Neves, Luís C.B.G. (University of Pretoria, 2024)
Dissertation (MSc (Global One Health))--University of Pretoria, 2023.